(3QSGFd GHf GdbGVis - (3YHO GdQMje Hf Ydj Hf GdSYjO GddNej, GdeYQha HGdbGVj GdaGVd,J (B596 (3g` s
(3ChdgG (B:s
(3GdMeO ddg, hef NWg CjVkG(B: (3hai jhe GdCQHYGA (B17 (3Pi GdbYOI ef YGe (B1073(3g` hfMf HGdRGhjI GdHcQjI cJHJ ddabjg GdCLd eMeO GdYTQi Hf eMeOkG Hf CHj HcQ s
(3BNQgG (B:s
(3hCfTO CjVkG ddabjg GdYdGeI SjOi YHOGdhGMO GHf YGTQ dbO eOMhG aGSkG HCTjGA LeI ef GdYde hGdBOGH hGdOjf hGdSfI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B275 - (3U(B282s
(3gfGc Tc ai fSHI GdeNWhW ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B346 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B209s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B21 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeg (B- (3GdQHGW (B((3O (B487) s
Keywords: (3GdCOHs